Answer: .00604
Step-by-step explanation:
Hope this helps
G(x) = 2x + 2
g(a + h) - g(a) = 2(a+h) + 2 - (2(a) + 2)
g(a + h) - g(a) = 2a + 2h + 2 - 2a - 2
g(a + h) - g(a) = 2h + 2 - 2
g(a + h) - g(a) = 2h
Your final answer is a. 2h.
The answer should be 11 since adding all the x’s up before 13 equals 11
Answer:
False ,false,true, true and true
Step-by-step explanation:
Y = 2x - 17, comparing to y = mx + c, slope m = 2.
If perpendicular, the new slope would be -1/2, that is the negative reciprocal of 2.
And passing through (-8 , 1).
using y = mx + c, and x = -8, y = 1, m = -1/2
1 = -1/2*-8 + c
1 = 4 + c
1 - 4 = c
c = -3
y = mx + c, substituting m = -1/2, and c = -3, y = -(1/2)x - 3.
Option C.